FUTURE FOREIGN LANGUAGE TEACHERS' SOCIAL AND COGNITIVE COLLABORATION IN AN ONLINE ENVIRONMENT - Nike Arnold; Lara Ducate (Language Learning and Technology)
Discussion boards provide an interactive venue where new and future language teachers can reflect, evaluate, solve problems or simply exchange ideas (e.g., Bonk, Hansen, Grabner-Hagen, Lazar, & Mirabelli, 1996; DeWert, Babinski, & Jones, 2003; Kumari, 2001; Pawan, Paulus, Yalcin, & Chang, 2003). In addition, encouraging future teachers to learn with technology before teaching with it allows them to become comfortable using various computer applications. This article examines transcripts from a semester-long asynchronous discussion between foreign language methodology classes at two different universities. Social and cognitive presence in the discussions was analyzed using Garrison, Anderson, and Archer’s Framework of a Community of Inquiry (2001). The results indicate that students engaged in a high degree of interactivity as well as all types of social and cognitive presence. These findings indicate that students not only progressed in their cognitive understanding of the pedagogical topics, but also employed social presence, the more dominant of the two, to aid their discussions. The topics seemed to play an important role in the type of cognitive activity evident in the discussions. These results differ from those of studies which found that students did not engage in interactivity (Henri, 1995; Pena-Shaff & Nicholls, 2004) and others which noted low levels of social presence (Garrison, et al. 2001; Meyer, 2003).